2016
DOI: 10.1007/s12593-015-0197-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relation Between Impairment Rating by AMA Guide and Activity and Participation Based on ICF in the Patients with Hand Injuries

Abstract: The aim of this paper is to analyze the relation between components of disability with distinguished score of impairment, activity and participation questionnaire based on clinical data of persons with hand injuries. Impairment was evaluated by use of AMA guide 6th edition and disability by DASH questionnaire on Convenience sample of patients (N= 117), with chronic hand injuries. Linking and allocating items of the DASH were done based on the ICF Core Set for Hand Conditions and the opinions of a group of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, it has been reported that pain may not be directly associated with either instrumental support or social participation. Rather, the association may be fully by way of activity limitations, as reported in clinical OA, community OA samples, and other non‐OA samples (43–47). The findings of these previous studies suggest that limitations in undertaking tasks and activities of daily living play a critical mediating role in the relationship between pain and reduced social participation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that pain may not be directly associated with either instrumental support or social participation. Rather, the association may be fully by way of activity limitations, as reported in clinical OA, community OA samples, and other non‐OA samples (43–47). The findings of these previous studies suggest that limitations in undertaking tasks and activities of daily living play a critical mediating role in the relationship between pain and reduced social participation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no hand outcome measure that captures all the items from the ICF Hand Core Set, 36 the PRWHE covers all 3 domains of function based on the ICF. 35 Because participation is an overarching goal related to the level of impairment and activity and is highly influenced by personal and environmental factors, 37 , 38 it is appropriate to be evaluated as a different subscale. Therefore, when considering the CFA and theoretical models, the structure of the PRWHE is supported.…”
Section: Discussionmentioning
confidence: 99%
“…The content of four extracted subscales indicated that the PBQ could evaluate participation comprehensively in patients with hand injuries. Many standard outcome measures are used in practice and specially designed to evaluate participation; however, their items do not fully capture the construct of participation in patients with hand injuries [36]. There are also some generic measures to evaluate participation [37][38][39].…”
Section: Plos Onementioning
confidence: 99%